Convergence in the priorities of entrepreneurial values: Empirical evidence from Malaysia - Looi, K.H.; Kamarulzaman, Y. (Springer Verlag (Germany), 2014)
This study aims to contribute to the field of international entrepreneurship by investigating entrepreneurial values priorities of Malaysian entrepreneurs compared to Western entrepreneurs and whether the magnitude of each entrepreneurial value is the same across ethnicity and gender within Malaysia. This cross-disciplinary post-positivist study used the survey method which involved 243 Malaysian small- and medium-sized entrepreneurs from the country’s two largest ethnic groups—the Malays and Chinese. The results provide evidence of convergence in entrepreneurial value priorities for Malaysian and Western entrepreneurs, thus contributing to existing literature on the entrepreneurial values system. Malaysian Malay and Chinese entrepreneurs differ in the magnitude of self-direction and stimulation but there is no difference across gender. The theoretical implications are firstly, that the definition of international entrepreneurship may be expanded to reflect entrepreneurs’ primary motivation of self-direction. Secondly, knowing the similarities in values priorities and differences in magnitude of values increases the cultural intelligence of international entrepreneurs. The practical implications are academicians and trainers should avoid gender stereotyping and foster salient entrepreneurial values when designing academic curriculum and training programs. Finally, the policy implications are that policy makers should attract or target those who possessed these salient entrepreneurial values when constructing entrepreneurship policies.